Does docosahexaenoic acid supplementation in term infants enhance neurocognitive functioning in infancy? - Heaton, Alexandra E.; Meldrum, Suzanne J.; Foster, Jonathan K.; Prescott, Susan L.; Simmer, Karen (Frontiers in Human Neuroscience, 2013)
The proposal that dietary docosahexaenoic acid (DHA) enhances neurocognitive functioning in term infants is controversial. Theoretical evidence, laboratory research and human epidemiological studies have convincingly demonstrated that DHA deficiency can negatively impact neurocognitive development. However, the results from randomized controlled trials (RCTs) of DHA supplementation in human term-born infants have been inconsistent. This article will i) discuss the role of DHA in the human diet, ii) explore the physiological mechanisms by which DHA plausibly influences neurocognitive capacity and iii) seek to characterize the optimal intake of DHA during infancy for neurocognitive functioning, based on existing research that has been undertaken in developed countries (specifically, within Australia). The major observational studies and RCTs that have examined dietary DHA in human infants and animals are presented, and we consider suggestions that DHA requirements vary across individuals according to genetic profile. It is important that the current evidence concerning DHA supplementation is carefully evaluated so that appropriate recommendations can be made and future directions of research can be strategically planned.